EFEKTIVITAS LAYANAN KONSELING KELOMPOK DENGAN TEKNIK ABILITY POTENTIAL RESPONSE UNTUK MENINGKATKAN KEDISIPLINAN BELAJAR SISWA - Kusuma, Wira Aldi; Nuryanto, Iis Lathifah (Universitas Sanata Dharma, 2024)
Effectiveness of Group Counseling Services Using the Ability Potential Response Technique to Improve the Learning Discipline of Class. The purpose of this research is to determine the effect of the effectiveness of group counseling services using the ability potential response technique to improve student learning discipline, whether there are changes after this research was carried out or there were no changes at all after the research was carried out. The method used in this research is quanttative with a pre-experimental design research type in the form of one group pre-test post-test. The sampling technique used is Nonprobability Sampling with Purposive Sampling type. The data collection technique used in this research is a learning discipline questionnaire. The data analysis techniques used in this research are validity test, reliability test, normality test, homogeneity test, and t-test analysis. Based on the research results, it shows that the provision of Ability Potential Response technical group counseling services has an effect on increasing the learning discipline of class XI students majoring in Pedalangan and Theatre.